Physical and Chemical Stability Test of SNEDDS (Self-nanoemulsifying Drug Delivery System) and Nanoemulsion Ethyl Acetate Fraction of Garcinia mangostana L. - Liza Pratiwi; Achmad Fudholi; Ronny Martien; Suwidjiyo Pramono (Majalah Obat Tradisional, 2018)
The mangosteen peels (Garcinia mangostana L.) has high free radical scavengers activity. This study aims to determine the physical and chemical conditions that are formulated in SNEDDS and nanoemulsion preparations. SNEDDS was made with various concentrations of Tween 80, PEG 400, and Virgin Coconut Oil (VCO) with a ratio of 4,98:1,02:1. Nanoemulsions were made with the addition of water to SNEDDS. Stability observation results were analyzed by statistics. The results of physical stability test show that all test samples in the research, in nanoemulsion, SNEDDS fraction, base SNEDDS, SNEDDS vitamin E did not undergo separation, precipitation, cracking, and creaming. On the chemical stability test of nanoemulsion and SNEDDS fraction there is no difference between IC50 before and after storage. While on basic SNEDDS and vitamin E nanoemulsion there is a difference between IC50 before and after storage.